Hubungan Financial Deepening dan Pertumbuhan Ekonomi: Studi Empiris di Indonesia - Panjawa, Jihad Lukis; Widianingrum, Ira Fitriani (Jurnal Penelitian, 2018)
Financial deepening has been identified as one of the strategies which can accelerate the rate of development. Deepening the financial sector is one important step in the effort to develop the country's financial markets especially developing countries one of which Indonesia. In this research will identify is the relationship between finacial deepening, the exchange rate of rupiah, interest rates and economic growth in Indonesia year of 1985-2015. The approach used in this study is the causality granger. The results in this study was the performance of the financial sector is still shallow. Financial deepening and economic growth have a one-way relationship, namely economic growth affects the financial deepening. Evidence that the introduction of Demand-Following Hypothesis in Indonesia. The exchange rate of the rupiah and financial deepening do not influence each other, as well as economic growth and the exchange rate of the rupiah not influence each other.